Threshold Effects of Sovereign Debt : Evidence From the Caribbean - Drakes, Lisa.; Craigwell, Roland; Greenidge, Kevin; Thomas, Chrystol (Washington, D.C. : International Monetary Fund, 2012)
This paper addresses the issue of threshold effects between public debt and economic growth in the Caribbean. The main finding is that there exists a threshold debt to gross domestic product (GDP) ratio of 55-56 percent. Moreover, the debt dynamics begin changing well before this threshold is reached. Specifically, at debt levels lower than 30 percent of GDP, increases in the debt-to-GDP ratio are associated with faster economic growth. However, as debt rises beyond 30 percent, the effects on economic growth diminishes rapidly and at debt levels reaching 55-56 percent of GDP, the growth impacts switch from positive to negative. Thus, beyond this threshold, debt becomes a drag on growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet